Association of homocysteine with ventricular dilatation and brain atrophy in Parkinson's disease. Issue 3 (6th January 2014) - Sapkota, Shraddha; Gee, Myrlene; Sabino, Jennifer; Emery, Derek; Camicioli, Richard
ABSTRACT: Parkinson's disease (PD) patients are treated with levodopa (l ‐dopa) to help stabilize their impaired motor abilities; however, l ‐dopa leads to increased homocysteine (Hcy) levels, which may have a deleterious effect on brain structure and function. The purpose of this study was to examine the impact of increased Hcy concentration on global brain atrophy as determined by magnetic resonance imaging in PD patients and controls. The effect of high Hcy level on ventricular dilatation (percentage of intracranial volume [%ICV]) and total tissue volume (%ICV) was examined at baseline and longitudinally at 36 months. Age, sex, education, andl ‐dopa duration (in PD patients) were included as covariates. Elevated Hcy levels correlated positively with ventricular dilatation (%ICV) in the whole sample ( P  = 0.004) and in the PD group ( P  = 0.008). At baseline, adults with a high Hcy level (>14 μmol/L) had higher ventricular volume (%ICV) than adults with a low Hcy level (≤14 μmol/L) in the whole sample ( P  = 0.006) and in the PD group ( P  = 0.03), which persisted over 36 months in both the whole sample ( P  = 0.004) and the PD group ( P  = 0.03). PD patients with high Hcy concentrations had a greater rate of ventricular enlargement (%ICV) over time compared with those with low Hcy concentration ( P  = 0.02). Elevated Hcy concentration was associated with increased ventricular dilatation (%ICV) in PD patients. A larger sample with a broader age range and longer follow‐up is needed to establish the consequences of high Hcy level, including interactions with genetic and environmental risk factors, in PD. © 2014 International Parkinson and Movement Disorder Society